EVALUATION OF FOREIGN DIRECT INVESTMENT IMPORTANCE IN PROMOTING ECONOMIC DEVELOPMENT IN DEVELOPING COUNTRIES: Case studies of FDI in developing countries - Huseynova, Halima (Annals of Spiru Haret University. Economic Series, 2023)
This paper examines the relationship between foreign direct investment (FDI) and economic development in developing countries. The paper begins with an introduction that provides a brief overview of the research topic. The research methodology is then discussed, followed by an exploration of the theoretical approaches to FDI and economic development. Case studies of FDI in developing countries are presented and analyzed, providing insight into the impact of FDI on economic development. The analysis section of the paper examines the data collected from the case studies and discusses the findings. Singapore is taken as a case study to measure for better understanding of the impact of FDI on economic development in developing countries. Foreign direct investment and gross domestic product variables were used to measure this relationship. Gross domestic product is dependent and foreign direct investment is independent variable in the study. In conclusion, the paper provides a summary of the key points. The references section provides a list of sources used in the paper.